Promoter hypermethylation of the CFTR gene as a novel diagnostic and prognostic marker of breast cancer. (10th December 2019) - Liu, Kaisheng; Dong, Fajin; Gao, Hengyuan; Guo, Yaomin; Li, Haili; Yang, Fang; Zhao, Pan; Dai, Yong; Wang, Jianhong; Zhou, Wenbin; Zou, Chang
Abstract: Breast cancer is the most commonly diagnosed cancer and the leading cause of cancer‐related deaths among women. New biomarkers with definite diagnostic and prognostic efficacy are urgently needed. Here, we showed that the promoter of the cystic fibrosis transmembrane conductance regulator (CFTR) was hypermethylated in breast cancer. The messenger RNA level of CFTR was downregulated in breast cancer. Notably, all 19 breast cancer patients with hypermethylated CFTR were diagnosed with invasive carcinoma. Moreover, CFTR was upregulated in decitabine (10 μM) treated breast cancer cells. Overexpression of CFTR inhibited cell growth whereas knockdown of CFTR promoted cell invasion. In the tissue array analysis, the CFTR protein level decreased significantly in breast cancer and low CFTR protein level correlated with poor survival with a P ‐value of 0.034. Thus, promoter hypermethylation of the CFTR gene might be a novel diagnostic marker of breast cancer.